Pesticide application windows in the region of Uberlândia-MG, Brazil (Bioscience Journal, 2016)
The success of the pesticide application is subject to meteorological conditions. The objective of this work was to determine the application windows suitable for carrying out the application of pesticides, using as parameters the analysis of historical data (2009-2014) of air temperature, relative air humidity, wind speed, and rainfall of Uberlândia-MG. With an electronic spreadsheet, and using the ideal meteorological conditions for applying pesticides (an air temperature above 30°C, relative air humidity above 55%, wind speed between 3 and 12 km h-1, and rainfall data lower than 0.2 mm h-1) as a parameter, the data were crossed with the aim to determine the times of day that weather conditions were ideal to obtain better efficiency in the application. According to the results, the relative air humidity was the main restricting criterion for the application windows, which are concentrated, on average, between 18:00 and 12:00 in the summer, and between 24:00 and 9:00 in the winter. The number of viable hours for a good application varied from 35 in the first fortnight of September to 198 in the second fortnight of March, demonstrating the great variability among the application windows throughout the year, which makes the generic recommendations of spraying time inadequate if the month of the year is not taken into consideration.